Information design in multi-stage games - Miltiadis Makris; Ludovic Renou (Theoretical Economics, 2023)
This paper generalizes the concept of Bayes correlated equilibrium (Bergemann and Morris, 2016) to multi-stage games. We apply our characterization results to a number of illustrative examples and applications.
Keywords: C73; D82; 330; Bayes' correlated equilibrium; communication equilibrium; information design; information structures; Multistage games; revelation principle; sequential communication equilibrium